A STUDY ON THE NECESSITY OF VOCATIONAL CAREER COUNSELING IN EDUCATION - Carmen Gabriela SECARĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
A person’s fulfillment may be achieved only when the three levels: personal, family and professional interweave. In the dynamic society in which we live, the trend is to emphasize only one of these levels, in the prejudice of the others. Therefore, the term “workaholic” is very often used. This, namely having a job to consume almost all our time, is often associated with the idea of career.The concept of vocational career has recently appeared in Romania, along with the transition to a society founded on performance. A strong emphasis is laid on vocational career in multinational companies as the managers cover all the necessary stages when hiring an individual, their choice being founded on the convenient profile of the employee, suitable for the company needs. Thus, vocational motivation appears as a gain for both parts. The respect towards the employee is shown through the company concern for his career development. It is what is called in the specialty literature the paternalist model of welfare, promoted by David Guest. The reciprocity within a company will bring forth the desire of assertion, of improvement and implicitly of performance. In general, the choice of a career in a field or another is a subjective motivation, dictated by certain factors at a given time. The study carried out in this article is based on the administration of questionnaires in the attempt to discover which are the motivations of pupils and students in choosing a university, a profession, if such choice is based on judicious information or influence of subjective factors. Also, the role that skills and qualities of each plays in choosing the career path is not negligible, aiming to whether individuals are aware of their professional profile. The importance of vocational counselor in educational institutions, schools, universities is of great significance because it is a professional who can guide pupils and students objectively in choosing a future profession that is consistent with their abilities and skills.